2019
DOI: 10.1111/jcmm.14814
|View full text |Cite
|
Sign up to set email alerts
|

Systematic screening identifies a 2‐gene signature as a high‐potential prognostic marker of undifferentiated pleomorphic sarcoma/myxofibrosarcoma

Abstract: The Cancer Genome Atlas (TCGA) Research Network confirmed that undifferentiated pleomorphic sarcoma (UPS) and myxofibrosarcoma (MFS) share a high level of genomic similarities and fall into a single spectrum of tumour. However, no molecular prognostic biomarkers have been identified in UPS/MFS. In this study, by extracting data from TCGA‐Sarcoma (SARC), we explored relapse‐related genes, their prognostic value and possible mechanisms of the dysregulations. After systematic screening, ITGA10 and PPP2R2B were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…We also constructed two comprehensive nomograms with satisfactory AUCs (OS: 0.832–0.926, PFS: 0.776–0.874) based on independent variables to assess the deterioration and survival of patients. To date, numerous studies have developed signatures based on sequencing data to stratify sarcoma patients, including CINSARC [ 64 ], alternative splicing events [ 65 ], relapse-related genes [ 66 ], and lncRNA [ 67 ]. However, none of them has been applied in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…We also constructed two comprehensive nomograms with satisfactory AUCs (OS: 0.832–0.926, PFS: 0.776–0.874) based on independent variables to assess the deterioration and survival of patients. To date, numerous studies have developed signatures based on sequencing data to stratify sarcoma patients, including CINSARC [ 64 ], alternative splicing events [ 65 ], relapse-related genes [ 66 ], and lncRNA [ 67 ]. However, none of them has been applied in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al [14] evaluated 61 MFS and undifferentiated pleomorphic sarcoma (UPS). They found that increased ITGA10 and decreased PPP2R2B expression had independent prognostic value.…”
Section: Integrin-10mentioning
confidence: 99%
“…Ogura et al [31] observed that the average fraction of infiltrated CD8+ T cells was significantly higher in the better prognostic cluster in MFS. Hu et al [14] reported that a high level of CD4+ T-cell infiltration was associated with a significantly better relapse-free survival in UPS and MFS. They also found a moderate negative correlation between the 2-gene signature (increased ITGA10 and decreased PPP2R2B) and CD4+ T-cell infiltration.…”
Section: Immunotherapymentioning
confidence: 99%
“…Soft-tissue sarcomas are a group of heterogeneous and rare mesenchymal tumors with aggressive behavior. Tumor resection and radiotherapy are still the main treatments for non-metastatic sarcomas [ 1 ]. Although the 5-year overall survival (OS) rate is about 70% in sarcomas [ 2 ], poor prognosis is common with local recurrence [ 3 ].…”
Section: Introductionmentioning
confidence: 99%